2022
DOI: 10.3390/insects13010059
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impacts on the Potential Distribution of Apocheima cinerarius (Erschoff) (Lepidoptera: Geometridae)

Abstract: Among the impacts of ongoing and projected climate change are shifts in the distribution and severity of insect pests. Projecting those impacts is necessary to ensure effective pest management in the future. Apocheima cinerarius (Erschoff) (Lepidoptera: Geometridae) is an important polyphagous forest pest in China where causes huge economic and ecological losses in 20 provinces. Under historical climatic conditions, the suitable areas for A. cinerarius in China are mainly in the northern temperate zone (30–50°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Among these, the HS index and WS index are important factors leading to a decrease in the PGD of MFF under future climate conditions ( Figure 6 ). One limitation of the current study is that the CLIMEX model only considers climatic factors [ 45 ]. However, aside from climate, additional factors can influence the spread of pests, such as human activities, topographic changes, host plants, and natural enemies [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the HS index and WS index are important factors leading to a decrease in the PGD of MFF under future climate conditions ( Figure 6 ). One limitation of the current study is that the CLIMEX model only considers climatic factors [ 45 ]. However, aside from climate, additional factors can influence the spread of pests, such as human activities, topographic changes, host plants, and natural enemies [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the evaluation metrics of the SDMs merely represented the quality of the simulation rather than the actual distribution of the candidates, which indicated that the results obtained via the SDMs were probably phenomenological and not mechanistic [ 82 ]. In addition, although we included many environmental variables when building the SDMs, they were still insufficient to determine the true distribution conditions of the species because many other important variables were missing from our models, such as biological interactions [ 138 ], topography constraints [ 5 ], human activities [ 139 ], and natural enemies [ 140 ]. All of these factors play a significant role in their distribution locations and ranges, and, even under suitable biological and abiotic conditions, species may still lose their suitable distribution areas for some time [ 141 , 142 ].…”
Section: Discussionmentioning
confidence: 99%
“…CLIMEX can model environmental suitability for a species on a seasonal basis. It has been used to predict the distributions of many species of insects [ 47 ]. P. interpunctella has the characteristics of euryphagy and crypticity, and it is distributed all over the world, which indicates that it has a strong continuous transmission ability.…”
Section: Discussionmentioning
confidence: 99%